2011
DOI: 10.2217/fca.11.67
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine Versus Amiodarone for Prevention of Postoperative Atrial Fibrillation

Abstract: Postoperative atrial fibrillation (AF) is a major complication of cardiothoracic surgery, leading to significant consequences, including a higher rate of stroke, longer hospital stays and increased costs. Amiodarone is among the most widely used agents for prevention of postoperative AF. Ranolazine, a US FDA-approved antianginal agent, has been shown to effectively, safely prevent and terminate nonpostoperative AF in both experimental and clinical studies. In a recent publication, Miles and colleagues directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[35] Several small studies have shown that ranolazine in moderate doses significantly shortens the mean time of conversion from AF to sinus rhythm and also reduces the occurrence of AF in coronary artery bypass grafting (CABG). [3637383940]…”
Section: Role Beyond Anginamentioning
confidence: 99%
“…[35] Several small studies have shown that ranolazine in moderate doses significantly shortens the mean time of conversion from AF to sinus rhythm and also reduces the occurrence of AF in coronary artery bypass grafting (CABG). [3637383940]…”
Section: Role Beyond Anginamentioning
confidence: 99%
“…In addition, ranolazine has been proposed to possess antiarrhythmic potential [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] which was principally related to the inhibition of sodium current (I Na ), rapid delayed rectifier potassium current (I Kr ) and calcium current (I Ca ) [27,[46][47][48][49][50]. A suppression of ventricular tachycardias by ranolazine after non-ST-segment elevation myocardial infarction has been proven in the MERLIN-TIMI 36 trial [51].…”
Section: Ranolazinementioning
confidence: 99%